Inclusion of a deafblind student in a public school in Macapá, Amapá State (Research, Society and Development, 2020)
The aim of this paper is to socialize the schooling of a deafblind student in a school in Macapá, Amapá. We will present aspects of the teaching learning process, didactic resources, methodology, advances and difficulties. The student is a 10 years-old female, reported with deep deafness and blindness. She is studying at the 3rd year of Elementary I for the second time. The regular classroom teacher has a higher education level and has already been mentored by the Multifunctional Resource Room (MRR) teacher. However, this teacher says she has no other professionals to accompany students with difficulties, so the student does not attended classes. At MRR, the student was assiduous and communicated with the teacher through reference objects and tactile pounds. She played games and activities using tact and overlapping hands, and recognized the surroundings when conducted freely by the teacher. This teacher has college and postgraduate degrees and is pursuing a master's degree. We emphasize the importance of trained professionals to the deafblind person from an early age to higher education, because it is necessary to meet their needs, respecting and valuing their time and knowledge. However, there are still noticeable gaps in school to become inclusive, regarding the ability of providing access, permanence and completion of studies.